Հայերի կոտորածները Բիթլիսի նահանգում օսմանյան բանակի և այլ զինված կազմավորումների կողմից (1915 թ.) - Ա. Գ. Բասենցյան (ՀՀ ԳԱԱ հրատ.)
В массовых погромах армян в провинции Битлис принимали участие как османская армия, так и другие вооруженные формирования. Использование артиллерии во время массовой резни армян свидетельствует о том, что османская армия играла активную роль в данных преступлениях. The Ottoman army and other armed formations took part in the massacres of Armenians in the province of Bitlis. The use of artillery during the massacres testifies that the Ottoman army played an active role in these crimes.
Keywords: History; D History; AMS Armenian Massacres